(untitled) (Research, Society and Development, 2025)
Bread is one of the most widely consumed ancient foods in the world and is of great importance in human nutrition. Therefore, this study aimed to analyze sensory aspects, acceptance rates, paired comparison test and purchase intention between breads produced from biological and natural fermentation. This is an applied, quantitative, explanatory and experimental study carried out from October to December 2023. The sensory acceptance test was conducted with 99 untrained tasters using a structured nine-point hedonic scale. The attributes considered included: appearance; texture; flavor; acidity; aroma and crunchiness, while a five-point scale was applied to obtain purchase intention. Descriptive statistics were used to characterize the group and the Mann-Whitney U-test was used to test the difference between the attributes of the two kinds of breads, while purchase intention was obtained by proportion. The data was tabulated in Statistical Package for the Social Sciences (SPSS), version 25.0. The significance level adopted was p<0.05. The sample was predominantly female (77.6%), with a high school degree (58.2%), an income of up to one minimum wage (52.6%) and an average consumption of bread between 2 and 3 times a week. Among the attributes evaluated, only two did not show a significant difference, but in the acceptance analysis all the attributes obtained acceptance above 70%. In the paired comparison test, the majority preferred the biologically fermented bread, and the same preference was indicated in the purchase intention.